Current Problems In Hypertension (Journal of Pedagogical Inventions and Practices, 2024)
Hypertension, or high blood pressure, remains one of the most common and important problems of modern medicine. The disease affects millions of people around the world and is associated with a high risk of cardiovascular complications such as stroke, myocardial infarction, heart failure and chronic kidney disease. Despite the progress made in diagnosis and treatment, many aspects of hypertension continue to raise questions and need to be solved. Let's consider the main current problems associated with this disease.